Capillary electrophoresis using immobilized whole cells with overexpressed endothelin receptor for specific ligand screening - Yu H.-M. (2014)
A new capillary electrophoresis method using immobilized cells as the stationary phase has been developed. The power of this method is demonstrated by the separation and identification of endothelin antagonists on a capillary column coated by the transfected Chinese hamster ovary (CHO) cells with overexpressing endothelin receptors. The screening results are validated by functional assays suppressing the increase of intracellular calcium concentration induced by endothelin-1. Instead of making efforts in isolating protein receptors, the easily prepared whole-cell capillary column provides a superior tool on the basis of ligand/receptor affinity for a rapid screening of potent drug candidates from compound libraries. © 2004 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.